Studi Kasus Tentang Implementasi Nilai-Nilai Pancasila Pada Lembaga Pendidikan Islam Al-Azhar Tingkat SMA - Pristiwiyanto, Pristiwiyanto (Program Studi Pendidikan Agama Islam, 2020)
This study aims to describe the implementation of Pancasila values ​​at the high school level Al-Azhar Islamic education institution. The data source of this research is a team of student teachers and students of Al-Azhar High School, Menganti-Gresik. This type of research is a case study. For taking respondents using sampling techniques. Data collection techniques using observation, interview, and documentation methods. The data analysis in this study used a qualitative descriptive analysis. The results of this study indicate that: (1) SMA Al-Azhar, Menganti-Gresik has implemented the values ​​of Pancasila through school culture, namely religious character, discipline, social care, environmental care, tolerance, national spirit and democracy; (2) the role of schools in shaping the character of students is very large, because in the school culture there are values ​​and beliefs as well as basic assumptions that aim at creating a learning community and supporting improvements in school quality; (3) there are several obstacles, especially the low Pancasila values ​​in each student